Increasing the performance of a superconducting spin valve using a Heusler alloy - Kamashev, Andrey A.; Validov, Aidar A.; Schumann, Joachim; Kataev, Vladislav; Büchner, Bernd; Fominov, Yakov V.; Garifullin, Ilgiz A. (Beilstein Journal of Nanotechnology, 2018)
We have studied superconducting properties of spin-valve thin-layer heterostructures CoOx/F1/Cu/F2/Cu/Pb in which the ferromagnetic F1 layer was made of Permalloy while for the F2 layer we have taken a specially prepared film of the Heusler alloy Co2Cr1−xFexAl with a small degree of spin polarization of the conduction band. The heterostructures demonstrate a significant superconducting spin-valve effect, i.e., a complete switching on and off of the superconducting current flowing through the system by manipulating the mutual orientations of the magnetization of the F1 and F2 layers. The magnitude of the effect is doubled in comparison with the previously studied analogous multilayers with the F2 layer made of the strong ferromagnet Fe. Theoretical analysis shows that a drastic enhancement of the switching effect is due to a smaller exchange field in the heterostructure coming from the Heusler film as compared to Fe. This enables to approach an almost ideal theoretical magnitude of the switching in the Heusler-based multilayer with a F2 layer thickness of ca. 1 nm.
Keywords: ferromagnet; proximity effect; spin valve; superconductor